If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7(7-3y)=36+4y
We move all terms to the left:
-7(7-3y)-(36+4y)=0
We add all the numbers together, and all the variables
-7(-3y+7)-(4y+36)=0
We multiply parentheses
21y-(4y+36)-49=0
We get rid of parentheses
21y-4y-36-49=0
We add all the numbers together, and all the variables
17y-85=0
We move all terms containing y to the left, all other terms to the right
17y=85
y=85/17
y=5
| 12+4(2x-1)=16x | | (X/3+5/6)=7x/12 | | -7a−35=-49 | | −7a−35=-49 | | 3x4=67 | | 2x+17=8x-60 | | -4x+11x=35 | | r+48/4=2 | | 6x+5x-45=75+4x | | -5x+19=1/2(6x+8)+2 | | 24+3w=-27 | | 6x+2x=7x-8 | | j+15=26 | | 9x-8=8+7x | | 18−4x=10−2x | | 5−7y=-2y | | 20=1/4x+3 | | f-28=225 | | 5g=3g+6 | | 3a-6=45 | | -2+12x-2=32 | | 7x−3=4x−17x-3=4x-1 | | -6x+2=−5x+5 | | 2(4z-1)=3(z-3) | | 3y+27=-9 | | 27-7x=14+6x | | 5=1-v | | -2x-10=18 | | 6n+4-2n=8 | | -4+3x+x-4=8 | | -2+8=5-(11p+2) | | 3x-13=-52 |